IMPACT OF TaN/Ta BILAYER ON THE BULK RESISTIVITY OF COPPER LAYER AT VARIOUS SELF-ANNEALING TIME - Abd Rahman, M.N.; Ahmad, A.F.; Hashim, Z.S.; Muhamad, M.R.; Budi, E. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
Copper layer metallization in back-end -of line interconnect is widely adopted in integrated circuit manufacturing. One of the issues faced in most of integrated circuit manufacturing industry is the restriction of 12 hours maximum delay time between the copper seed deposition and copper electroplating step. This is due to claim of possible sheet resistance (Rs) instability as a result of copper diffusion into silicon even though with the presence of TaN/Ta bilayer barrier between silicon dioxide layer and copper layer. There is lack of study and data to justify support this time restriction or on the effectiveness of the TaN/Ta bilayer barrier in stabilizing sheet resistance of copper layer as a function of self-annealing time. This study evaluates the effectiveness of Ta/TaN barrier to prevent changes in Rs of copper seed layer as a function of self-annealing time. The result indicates that the The TaN/Ta bilayer barrier improve the stability of Rs of the copper seed layer at various level of self-annealing time. However, the t-test analysis shows that at 95% confidence level, statistically there is significant drop in Rs for both experimental lots (with and without TaN/Ta bilayer barrier) comparing the 0 hour and 12 or 36 hour of self-annealing time.